2020
DOI: 10.1002/cctc.201902035
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Water Oxidation Catalyzed by N4‐Coordinate Copper Complexes with Different Backbones: Insight into the Structure‐Activity Relationship of Copper Catalysts

Abstract: Copper complexes with a general formula of [(L)Cu(OH2)](BF4)2 (1, L1=N,N′‐dimethyl‐N,N′‐bis(pyridin‐2‐ylmethyl)‐1,2‐diaminoethane; 2, L2=N,N′‐bis(pyridin‐2‐ylmethyl)piperazine); 3, L3=N,N′‐bis(pyridin‐2‐ylmethyl)diazepane) were prepared as molecular catalysts for oxygen evolution reaction. These catalysts have the same first coordination environment but different backbones of diamine‐dipyridine N4‐ligands. Single crystal X‐ray diffraction studies on the molecular structures of 1–3 revealed that the backbone ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 43 publications
0
28
0
Order By: Relevance
“…The formation of the O–O bond by the reaction of Cu( iv )O species with the water molecule is widely regarded as the rate-limiting step for oxygen evolution via a mononuclear catalytic mechanism. 10,13,14,22 Electrochemical measurements reveal that the N–H structure of the amine containing ligand of complex 2 is favourable for the generation of [Cu IV O(L)] 2+ species. Additionally, the electron-withdrawing group on the ligand results in higher reactivity of some MO intermediates (M is the transition metal) in the water oxidation catalytic cycle mediated by the metal complex while the electron-donating group on the ligand is exactly the opposite.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The formation of the O–O bond by the reaction of Cu( iv )O species with the water molecule is widely regarded as the rate-limiting step for oxygen evolution via a mononuclear catalytic mechanism. 10,13,14,22 Electrochemical measurements reveal that the N–H structure of the amine containing ligand of complex 2 is favourable for the generation of [Cu IV O(L)] 2+ species. Additionally, the electron-withdrawing group on the ligand results in higher reactivity of some MO intermediates (M is the transition metal) in the water oxidation catalytic cycle mediated by the metal complex while the electron-donating group on the ligand is exactly the opposite.…”
Section: Resultsmentioning
confidence: 99%
“…9 Moreover, research on the influence of the first- and second-coordination spheres on metal complexes for catalytic water oxidation can provide guidelines for the design of efficient catalysts for other catalytic systems, such as artificial photosynthesis. 10,11…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[190] Shen et al also reported a Cu complex with a diamine-dipyridine ligand (Cu-24) that promoted the electrochemical oxygen evolution reaction. [191] Meyer and co-workers explored the electrochemical properties of a single-site Cu complex (Cu-25) with a rugged ligand. [192]…”
Section: Mononuclear Cu Complexes With Tetradentate Non-macrocyclic L...mentioning
confidence: 99%
“…[28][29][30][31][32][33][34] Recently, copper complexes have joined the short list of molecular catalysts for the WOR. [35][36][37][38][39][40][41][42][43] Reasons behind this stem from the copper oxygenase functions where O 2 activation leads to the cleavage of the O-O bond leading to highly oxidized copper species. 44 Hence reversing the activation steps from H 2 O to form O-O bond is an attractive perspective.…”
Section: Introductionmentioning
confidence: 99%